Proton transfer from 2-naphthol to aliphatic amines in supercritical CO 2 - Simoncelli, Sabrina (2011)
The proton transfer from 2-naphthol to aliphatic amines was studied in supercritical CO 2 (scCO 2) and in cyclohexane as reference solvent, by absorption and fluorescence spectroscopy and by time-resolved emission. Irradiation of 2-naphthol in scCO 2 in the presence of ethyldiisopropylamine shows dynamic fluorescence quenching of the acidic form of 2-naphthol and emission from the basic form. Fluorescence excitation spectra show that the emission of the basic form is originated upon excitation of the acidic form. The interaction between 2-naphthol and the amines is described by the formation of a complex with proton donor - acceptor character in the ground and excited states of 2-naphthol. The acidity increase of 2-naphthol upon electronic excitation to the first excited singlet in scCO 2 is as high as in water. Proton transfer quantum yields of 0.6 can be easily achieved in scCO 2. The results have implications for carrying out acid - base catalyzed reactions in scCO 2. (Figure presented) © 2011 American Chemical Society.